1985
DOI: 10.1029/jc090ic06p11765
|View full text |Cite
|
Sign up to set email alerts
|

The evolving structure of an upwelling filament

Abstract: The evolution of an upwelling filament was studied over a 2-week period by using satellite infrared images, and its thermohaline structure was mapped in situ. The surface velocity field consisted of a large meander extending offshore for at least 300 km.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(136 citation statements)
references
References 15 publications
(10 reference statements)
9
123
0
Order By: Relevance
“…In the mixed layer, abundant examples of horizontal fronts with temperature and salinity that nearly cancel in their joint effect on density can be found on scales of 10-100 km [i.e., Roden, 1975Roden, , 1989Yuan and Talley, 1992). A few observations have been made of horizontal density fronts on scales finer than 10 km in which the temperature gradient is partially opposed by the salinity gradient [e.g., Flament et al, 1985;Rudnick and Luyten, 1996]. A useful measure of the degree of compensation is the density ratio R defined as the ratio of the relative effect of temperature and salinity on density over a spatial interval.…”
Section: Introductionmentioning
confidence: 99%
“…In the mixed layer, abundant examples of horizontal fronts with temperature and salinity that nearly cancel in their joint effect on density can be found on scales of 10-100 km [i.e., Roden, 1975Roden, , 1989Yuan and Talley, 1992). A few observations have been made of horizontal density fronts on scales finer than 10 km in which the temperature gradient is partially opposed by the salinity gradient [e.g., Flament et al, 1985;Rudnick and Luyten, 1996]. A useful measure of the degree of compensation is the density ratio R defined as the ratio of the relative effect of temperature and salinity on density over a spatial interval.…”
Section: Introductionmentioning
confidence: 99%
“…These filaments are associated with narrow baroclinic jets that form over the continental shelf and flow offshore advecting cold, upwelled water into the open ocean. They are easily identified by their temperature signatures in satellite images of Sea Surface Temperature (SST) (Flament, Armi, & Washburn, 1985). Many projects have focussed on filaments in recent years in Eastern Boundary Systems (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The northern boundaries, hereinafter called d-type boundaries (for diffuse transition), usually exhibit a smoother, more diffuse transition in SST from the warm water north of the filament into the filament's center. Both density compensated (e.g., Flament et al, 1985;Kosro and Huyer, 1986;Rienecker and Mooers, 1989) and non-density compensated (e.g., Kosro and Huyer, 1986;Reinecker et al, 1985;Ramp et al, 1991) s-type boundaries have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Their discussion, however, was not framed in terms of the d-type/s-type nature of oceanic fronts in these regions. Because convergence and subduction appears to occur near intense s-type boundaries (e.g., Flament et al, 1985;, it is possible that albacore orient themselves in order to take advantage of these processes. The subduction process may transport prey out of the nutrient rich filament and into clear warm water offshore.…”
Section: Acoustic Propagation In the Oceanmentioning
confidence: 99%
See 1 more Smart Citation